Designing Clothes that Meet the Functional and Aesthetic Needs of Children with Hip Dislocation (Al-Academy, 2021)
Children who have a health problem need special requirements for their clothes. The purpose of the study is to design functional and aesthetic clothes to meet their needs. The research used the applied descriptive approach. The research sample comprised 120 women whose children suffered from hip dislocation. Designs for injured children presented and submitted to the arbitrators for evaluation regarding the functional and aesthetic aspects. The finding was achieving the design solutions. The most important recommendations are to increase attention to designing clothes to suit all the needs of society.